Description of a new species of myxobolid parasite, Henneguya pindaibensis n. sp. (Cnidaria: Myxosporea), infecting the gills of Boulengerella cuvieri (Spix and Agassiz, 1829) from Brazil - Úngari, Letícia Pereira [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; de Alcantara, Edna Paulino [UNESP]; Emmerich, Enzo [UNESP]; Santos, André Luiz Quagliatto; da Silva, Reinaldo José [UNESP]; O'Dwyer, Lucia Helena [UNESP] (Elsevier, 2021)
Myxozoans are microscopic cnidarians that mainly parasitize fishes. The present study aimed to describe a new myxozoan parasite from the gills of Boulengerella cuvieri (Spix and Agassiz, 1829) by morphological and molecular analysis. The fish was collected in 2019 at the Pindaíba River, municipality of Cocalinho, Mato Grosso State, Brazil. Whitish and circular plasmodia were found in the primary gill filaments, occupying an intralamellar position, with an average of 0.5 mm in diameter. Henneguya Thélohan, 1892 myxospores found inside the plasmodia were elongated and ellipsoidal, consisting of two long and elliptical shell valves with two long, tapering caudal appendages. Morphometric measurements revealed a total spore length of 36.1 ± 2.0 μm; spore body length of 12.8 ± 0.5 μm; spore width of 4.9 ± 0.3 μm; tail length of 23.3 ± 1.6 μm; capsule length of 7.2 ± 0.4 μm; capsule width of 1.5 ± 0.2 μm; and 10 coils in the polar filament. Phylogenetic analysis showed that the isolates from this study were grouped into the main-clade of freshwater fishes, within a group of species parasitizing fishes from Brazil. Intergenotypic difference ranged from 23%–25.9% compared with other Brazilian myxozoan isolates. Using molecular and morphological characterization, this parasite was identified as a new species of the genus Henneguya.
Keywords: Ctenoluciidae; Myxobolidae; Phylogeny; SSU rDNA